Pengaruh Locus Of Control, Gaya Kepemimpinan, Komitmen Organisasi dan Etika Profesi terhadap Kinerja Auditor: Studi Kasus BPKP Maluku - Hukom, Widya Frisca; Atarwaman, Rita J.D; Usmany, Alfrin Ernest Marthen (Accounting Research Unit (ARU Journal), 2024)
This research aimed to understand influence of Job Satisfaction, Professionalism, Leadership Style, and Application of Information Technology towards Auditor Performance. Data was obtained by spreading questionaires to the auditors who work at BPKP of Maluku Representation Office. The questionaires were spreads to 62 respondents, but only 40 respondents which the data could be analyzed and processed. Data analysis of the research used multi-linear regression analysis. This research is consisted of dependent and independent variables. The dependent variable is Auditor Performance, and the independent variables are Locus Of Control, Leadership Style, Organizational Commitment and Professional Ethics. The result shows that Organizational Commitment has a negative effect on Auditor Performance, Leadership Style doesn't have effect on Auditor Performance. But another variable that is Locus Of Control and Professional Ethics have a positive and significant effect on Auditor Performance.